A especulação imobiliária na valorização dos imóveis na cidade de Mossoró-RN - Costa, Nilton Menezes (Universidade Federal Rural do Semi-Árido, 2018)
The present work aims to analyze the formation of the real estate market in the city of Mossoró/RN, seeking to characterize the process of real estate speculation and its effects, as well as to present information about the current scenario of the real estate market of the city. The hypothesis of research is that the real estate expansion registered in the city of Mossoró was vigorously accompanied by the process of real estate speculation. This process is responsible for triggering impacts and effects on real estate prices, due to the search for capital expansion by speculation. However, the consequence of this phenomenon affects negatively on part of the population in need of the city, due to the increase in urban land and real estate. The applied methodology in the work contemplates secondary and field research. For this, a review of the literature was carried out with the objective of exploring the historical construction of the Mossoró real estate market, emphasizing aspects of speculation and real estate cycles to understand the dynamics of this market. As for the field research, this was done through the use of interviews with important economic agents involved with the real estate activity in the city. The results showed that there was an important real estate expansion in the city, mainly in recent years, which resulted in an increase in prices and appreciation of urban land. Finally, it was verified that the city of Mossoró, although it is one of the cities of the interior of Rio Grande do Norte that more urban sprawl, is going through a strong moment of crisis in the real estate and civil construction sector, caused by the bad phase of the entire national territory.
Monografia
Keywords: Construção civil; Minha casa, minha vida; Especulação imobiliária; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA